Relevansi Perdebatan Liberalisme Versus Komunitarisme Untuk Konteks Indonesia - Otto Gusti Madung (Millah: Journal of Religious Studies, 2012)
The crisis of solidarity on the one hand and political identity that denies the diversity on the other hand is a big problem that plagued the nation’s center of Indonesia. This issue is trying to read in a philosophical discourse about the glass eye kommunitarism versus liberalism. The debate between these two philosophies can be drawn mazhab its relevance to the context of Indonesia. Here, Pancasila occupies a special position.